Model of the Relationship of Religiosity and Happiness of Multiple Sclerosis Patients from Poland: The Role of Mediating and Moderating Variables - Wnuk, Marcin (Religions, 2022)
Religiosity and spirituality can be both beneficial and harmful to happiness. It depends on its operationalization and the measures of religiosity and sociodemographics used, together with cultural and psychosocial factors, still not comprehensively explored. This topic is especially important for religious-affiliated chronic patients such as those diagnosed with multiple sclerosis. Religion can deliver a sense of meaning, direction, and purpose in life and be an additional source of support to cope with the stress and limitations connected with the disease. The aim of the present study was to verify whether religiosity, directly and indirectly, through finding meaning in life, is related to one’s level of happiness and whether gender, the drinking of alcohol, financial status, and age are moderators in this relationship. In sum, 600 patients from Poland who suffered from multiple sclerosis were included in the study. Firstly, some gender differences were noticed. In women, religiosity was both directly and indirectly, through finding significance, positively related to happiness. Secondly, it was found that in women, the direct effect of age on happiness was generally negative but was positively affected by religiosity; however, among men, age was not correlated with happiness. In the group of women, religiosity and a lower propensity to drink alcohol in an interactive way explained happiness. Thirdly, both in men and women, financial status positively correlated with happiness, but in the group of wealthy men only, religiosity was negatively related to happiness. In conclusion, religion was found to show a positive correlation with the happiness of Roman Catholic multiple sclerosis patients from Poland. In this group of patients, religious involvement can be suggested and implemented as a factor positively related to happiness, with the one exception regarding wealthy men.